The Plant Bioacoustics: A system of plant-sound relationship - Nakade, Divya; Dhadse, Sharda (Plantae Scientia, 2024)
Bioacoustics is a field of study that examines the production of sound and how it affects living things. Numerous plant species' physiology, behaviour, and eventual survival have all been greatly influenced by sound and its usage in communication. A better framework for future research may be developed along with a greater understanding of how various organisms interact acoustically with plants if the acoustic link between plants and animals is understood. A re-imagination of our knowledge of these organisms is anticipated to result from the systematic investigation of the functional and evolutionary importance of sound in plant life. This will also stimulate the emergence of new ideas and viewpoints regarding the communicative complexity of plants. The primary goal of this study is to examine some information about the bioacoustics interaction between plants and animals their sound, and ecology, including potential techniques of sound production employed by plants. The importance of acoustical research in plant ecology, as well as its potential mechanisms and future applications, are covered in this paper. The first section of this article reviews how plants amplify and transmit sounds produced by insect pests. The second section looks at surprising examples of carnivorous plants that show how plants have evolved to reflect but also enhance animal sounds, potentially revealing new angles in research on the interactions between animals and plants. The discussion then focuses on the mechanisms by which plants produce sound through transpiration stress and photosynthesis, as well as a potential model for these mechanisms.